(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Annyuk O. A. Formation of motivational-need sphere of future teachers in the process. of teaching at a pedagogical institute The article discusses the conditions of formation of the need-motivotional sphere of future teachers in the process of studying in the pedagogical institute.